Uromodulin and Vesico-Ureteral Reflux: A Genetic Study - Silvio Maringhini; Rosa Cusumano; Ciro Corrado; Giuseppe Puccio; Giovanni Pavone; Maria Michela D’Alessandro; Maria Chiara Sapia; Olivier Devuyst; Serena Abbate (Biomedicines, 2023)
Vesicoureteral reflux (VUR) is associated with urinary tract infections (UTI) and renal scars. The kidney damage is correlated with the grade of reflux and the number of UTI, but other factors may also play a role. Uromodulin (UMOD) is a protein produced by kidney tubular cells, forming a matrix in the lumen. We evaluated whether the common variant rs4293393 in the UMOD gene was associated with febrile UTI (FUTI) and/or scars in a group of children with VUR. A total of 31 patients with primary VUR were enrolled. Renal scars were detected in 16 children; no scar was detected in 15 children. Genotype rs4293393 TC (TC) was present in 8 patients, 7 (88%) had scars; genotype rs4293393 TT (TT) was found in 23 patients, and 9 (39%) had scars. Among children with scars, those with TC compared with those with TT were younger (mean age 77 vs. 101 months), their reflux grade was comparable (3.7 vs. 3.9), and the number of FUTI was lower (2.9 vs. 3.7 per patient). Children with VUR carrying UMOD genotype rs4293393 TC seem more prone to developing renal scars, independent of FUTI.